Exploring Inclusive Media: Frameworks for Barrier-Free Audio-Visual Communication in China - Shuai, Fu; Somia Abdul Same’e (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
Accessible audio-visual communication media can be categorized into two main types: dedicated accessible online audio-visual apps and modified accessible apps. Despite the presence of policies promoting the barrier-free transformation of apps, only a limited number of media platforms effectively meet the needs of people with disabilities. Furthermore, research on the effectiveness of accessible audio-visual communication is scarce, highlighting the need for a comprehensive evaluation system to assess its impact on disabled users. This paper proposes a practical pathway for enhancing accessible audio-visual communication, centered on four subsystems: users, services, products, and platforms.